A 10-year follow-up study of the cardiovascular risk factors in children aged 6–16 years. (14th October 2021) - Triantafyllidi, H; Dretsiou, E; Benas, D; Trivilou, P; Pavlidis, G; Ikonomidis, I; Iliodromitis, E
Abstract: Background: Obesity and arterial hypertension in children represent well recognized risk factors for future cardiovascular (CV) events during early adult life. We aimed to investigate any changes regarding several parameters affecting the CV status of children aged 6–16 years after a 10-year follow-up period. Methods: A cohort of 143 children 6–16 years old (79/64 boys/girls, mean age 9±2 years) was evaluated regarding food habits (fish/chicken/vegetables/fruit per week), obesity (BMI), office blood pressure (SBP/DBP), aortic stiffness (PWV), lipid profile (HDL, LDL) and sports activity (hours of exercise/week). After a 10-years follow-up period, we managed to re-evaluate 62/143 (43%) young adults (33/31 boys/girls, mean age 20±2 years) for the same parameters plus endothelial function estimated by endothelial glycocalyx integrity (PBR5–25). Results: We found that after 10 years, young adults compared to themselves had increased BMI, SBP/DBP and PWV (p<0.001), decreased HDL and LDL (p<0.001 and p=0.004, respectively), increased consumption of chicken and vegetables (p<0.001 and p=0.05, respectively) and decreased consumption of fish and fruits (p=0.004 and p=0.001, respectively) per week and finally increased weekly hours of sports activity (p=0.005). Mean PBR5–25 was 1.9±0.2 μm. Regarding obesity, the majority of children were overweight (20%) or obese (41%) while the majority of young adults were normoweight (60%) and only 11% obese. Regarding arterial hypertension (mean value of a triple office BP measurement), we measured BP >95th percentile in 7% of the children (50% of children had finally white coat hypertension) while just one young adult (2%) had BP >140 mmHg). Conclusions: After 10 years, children became young adults with an improved status regarding obesity, normal BP levels, favorable lipid profile as for LDL levels, almost healthy food habits who also spend more hours in sport activities. However, HDL was decreased, aortic stiffness was increased while there are no comparable data regarding endothelial glycocalyx integrity. Overall, the profile of young adults seems protective against future CV events. Funding Acknowledgement: Type of funding sources: None.